Glucocorticoids promote CCL20 expression in keratinocytes. (17th August 2021) - Wang, L.; Yang, M.; Wang, X.; Cheng, B.; Ju, Q.; Eichenfield, D.Z.; Sun, B.K.
Summary: Background: Glucocorticoids (GCs) are generally envisioned as immunosuppressive, but in conditions such as rosacea and perioral dermatitis they can lead to increased skin inflammation. In lung epithelia, GCs promote expression of the proinflammatory cytokine CCL20, which contributes to steroid‐resistant asthma. In the skin, CCL20 stimulates inflammation by recruiting T helper 17 T lymphocytes and dendritic cells, and is elevated in papulopustular rosacea. Objectives: To understand if, and how, GCs affect CCL20 expression in human keratinocytes. CCL20 expression was assessed by quantitative reverse transcriptase polymerase chain reaction and enzyme‐linked immunosorbent assay. Methods: Selective inhibition of candidate genes and signalling pathways was performed using RNA interference and chemical inhibitors. The binding of activated GC receptor to genomic DNA was determined by chromatin immunoprecipitation, and enhancer activity of genomic sequences was measured with a reporter assay. Results: We found that GC treatment increased CCL20 expression in human keratinocytes and murine skin, both in the undisturbed state and with tumour necrosis factor‐α stimulation. GC repressed proinflammatory signalling pathways, including nuclear factor kappa B and p38/mitogen‐activated protein kinase, but these inhibitory effects were opposed by the direct binding of activated GC receptor to the CCL20 enhancer, promoting CCL20 expression. Conclusions: Viewed together, these findings demonstrate a mechanism by which GCs induce expression of CCL20 in keratinocytes, which may contribute to the inflammation seen in steroid‐exacerbated skin conditions. Abstract : What is already known about this topic? Glucocorticoids (GCs) are generally considered immunosuppressive but can actually worsen some inflammatory skin conditions such as rosacea and perioral dermatitis. In bronchial epithelia, GCs promote the expression of the proinflammatory cytokine CCL20, which contributes to steroid‐insensitive asthma. Increased CCL20 is associated with the inflammation of rosacea, but whether GCs induce its expression in the skin is unknown. What does this study add? This study demonstrates that activated GC receptor directly binds the CCL20 enhancer in human keratinocytes to promote its expression. What is the translational message? GCs can directly activate the expression of CCL20, which may help explain how topical steroids can worsen skin conditions such as perioral dermatitis and rosacea. Linked Comment:  R.F.L. O'Shaughnessy. Br J Dermatol 2021; 185 :1091–1092 .